Temporal and spatially controlled APP transgene expression using Cre-dependent alleles - Emily J. Koller; Melissa Comstock; Jonathan C. Bean; Gabriel Escobedo; Kyung-Won Park; Joanna L. Jankowsky (The Company of Biologists, 2022)
Although a large number of mouse models have been made to study Alzheimer's disease, only a handful allow experimental control over the location or timing of the protein being used to drive pathology. Other fields have used the Cre and the tamoxifen-inducible CreER driver lines to achieve precise spatial and temporal control over gene deletion and transgene expression, yet these tools have not been widely used in studies of neurodegeneration. Here, we describe two strategies for harnessing the wide range of Cre and CreER driver lines to control expression of disease-associated amyloid precursor protein (APP) in modeling Alzheimer's amyloid pathology. We show that CreER-based spatial and temporal control over APP expression can be achieved with existing lines by combining a Cre driver with a tetracycline-transactivator (tTA)-dependent APP responder using a Cre-to-tTA converter line. We then describe a new mouse line that places APP expression under direct control of Cre recombinase using an intervening lox-stop-lox cassette. Mating this allele with a CreER driver allows both spatial and temporal control over APP expression, and with it, amyloid onset. This article has an associated First Person interview with the first author of the paper.